2014
DOI: 10.1371/journal.pntd.0003125
|View full text |Cite
|
Sign up to set email alerts
|

Ring-Screening to Control Endemic Transmission of Taenia solium

Abstract: Background Taenia solium is a major cause of preventable epilepsy in developing nations. Screening and treatment of human intestinal stage infection (taeniasis) within high-risk foci may reduce transmission and prevent epilepsy by limiting human exposure to infective eggs. We piloted a ring-strategy that involves screening and treatment for taeniasis among households located nearby pigs heavily-infected with the larval stage (cysticercosis). These pigs mark areas of increased transmission and can be identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 30 publications
0
60
0
Order By: Relevance
“…Nonetheless, if the greater sensitivity of ultrasound represents a true difference, it could have an impact on ring interventions given the high reproductive capacity of the adult stage tapeworm and the potential for an untreated case to reverse control gains. In a recent investigation that allocated treatment rings based on tongue-positivity in pigs, the prevalence of taeniasis at study end was 1.4% in the treatment arm [16]. While this was significantly less than the prevalence in the control arm (2.5%), the majority of remaining taeniasis carriers went untreated because they did not fall into treatment rings, suggesting a potential underdiagnosis of heavily infected pigs in this trial.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Nonetheless, if the greater sensitivity of ultrasound represents a true difference, it could have an impact on ring interventions given the high reproductive capacity of the adult stage tapeworm and the potential for an untreated case to reverse control gains. In a recent investigation that allocated treatment rings based on tongue-positivity in pigs, the prevalence of taeniasis at study end was 1.4% in the treatment arm [16]. While this was significantly less than the prevalence in the control arm (2.5%), the majority of remaining taeniasis carriers went untreated because they did not fall into treatment rings, suggesting a potential underdiagnosis of heavily infected pigs in this trial.…”
Section: Discussionmentioning
confidence: 81%
“…Since ultrasonography and tongue examination have poor sensitivity at lower cyst burdens, neither is an adequate screening tool for evaluating food safety or for monitoring progress of control programs. Results from several necropsy studies in endemic villages have shown that the vast majority of pigs infected with cysticercosis have less than 10 cysts in the entire carcass [1618]. Neither ultrasonography nor tongue examination was able to accurately diagnose pigs with burdens of infection less than 100 cysts, detecting just 8% (3/36) and 3% (1/36) of these infected pigs respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This "bottom-up" structure allows for the modeler to easily manipulate the behaviors or the modeled environment and observe the emergent patterns that are produced by such manipulations. In the context of T. solium transmission, this structure facilitates application of the model to a variety of transmissions settings, and allows for testing a wide range of available control strategies, including spatially targeted strategies (e.g., "Ring Strategy" [28]), and other behavioral and structural interventions.…”
Section: Introductionmentioning
confidence: 99%